HARDWARE QPSK IMPLEMENTATION BASED ON ZYNQ AND MATLAB - Skabylov, А.А; Ibraimov, М.К; Zhaxebay, Д.М.; Kozhagulov, Е.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The requirements for a mobile network are growing with the increase of wireless devices. In connection with the existing large flow of information in the environment around us, it is urgent to create high-speed, noise-resistant, simple to implement and economical devices for receiving and transmitting information data. For the development of high-speed, wideband radio modules, the most suitable hardware is programmable logic integrated circuits. The possibility of parallel computing and the large number of logical cells in these digital devices give a relatively high performance for all equipment. Moreover, the built-in microprocessor in an integrated microcircuit makes it possible to create the most high-performance telecommunication equipment. In this paper, a QPSK (quadrature phase manipulation) signal transceiver based on SoC (system on a chip) has been developed. The QPSK models of the transmitter and receiver were used to interact with the ZedBoard board and the AD-FMCOMMS3-EBZ RF platform. the constructed digital radiosystem had been demonstrated using system on a chip, which model correspond to the radio module of modern telecommunication techniques.